Echovis – A collection of human echolocation tests performed by blind and sighted individuals: A pilot study - Bujacz, Michał; Królak, Aleksandra; Górski, Grzegorz; Matysik, Krzysztof; Witek, Piotr (The British journal of visual impairment, 2023)
The article presents research on the echolocation skills of blind and sighted individuals gathered for the purpose of development of an echolocation training app. The goal of the research was to determine the influence of the environment type, reverberation, clicking patterns, and the average differences between the two tested groups. Ten blind and 10 sighted subjects were tested in various echolocation tasks – stationary, moving, indoor and outdoor, using mechanical clickers, and artificially generated clicks. Ten blind children also took part in the static indoor tests. The tests were repeated using binaural recordings and spatially rendered virtual audio. The following parameters and dependencies between them were analyzed: correctness of the obstacle localization, certainty of answer, type of environment and clicker sound, and frequency and number of clicks. It was found that the number of clicks influenced the correctness and certainty of the answer in case of obstacle direction determination, but not the distance. Better results were obtained in outdoor environments and in an empty room, what implies that reverberation has a positive influence on echolocation. The expected success rates in tested echolocation tasks provided a comparison of the echolocation abilities of blind and sighted subjects and set a benchmark for future tests.